Tungsten-copper shaped charge liner and preparation method thereof

By optimizing the morphology and particle size grading of tungsten powder and copper powder, and adding modifiers and energy-containing materials, the problems of uneven density distribution and poor jet performance of tungsten copper drug masks are solved, and high density and depth jet effects are achieved, meeting the high requirements of petroleum perforation.

CN119876723AActive Publication Date: 2025-04-25XIAN RARE METAL MATERIALS RES INST CO LTD

Patent Information

Application Number
CN202510361071.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

The density distribution of existing tungsten copper pharmaceutical covers is uneven and the particle size is unreasonable, resulting in poor jet performance and cannot meet the high requirements of the oil perforation energy-generating armor-breaking warhead for jet penetration depth.

Method used

By optimizing the morphology and particle size grading of tungsten powder and copper powder, and adding modifiers and energy-containing materials, the modified powder has good uniformity and fluidity, thereby improving the molding performance of the tungsten copper pharmaceutical mask and the depth of jet penetration.

Benefits of technology

The density of the tungsten copper drug mask has been increased to 92%~99%, and the penetration depth of the static armor-breaking test has reached more than 760mm, meeting the demand for oil perforation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a tungsten-copper shaped charge liner which comprises the following raw materials in parts by mass: 70-90 parts of tungsten powder, 10-30 parts of copper powder and 2-10 parts of an energetic material, the preparation method of the tungsten-copper shaped charge liner comprises the following steps: 1, mixing tungsten powder, copper powder and an energetic material to obtain a mixture, and dissolving a lubricant and a modifier with a solvent to obtain a solution; 2, adding the solution into the mixture, carrying out heat preservation and stirring for modification, and carrying out drying and sieving to obtain modified powder; and thirdly, the modified powder is formed to obtain a shaped charge liner blank, and the tungsten-copper shaped charge liner is obtained through degreasing and sintering. According to the tungsten-copper shaped charge liner, by optimizing the morphology and grain size distribution of the tungsten powder and the copper powder and adding the energetic material and the modifier, it is ensured that the modified powder has good uniformity and fluidity, so that the tungsten-copper shaped charge liner has excellent forming performance, meanwhile, the density and penetration depth of the tungsten-copper shaped charge liner are improved, and the requirement for petroleum perforation can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tungsten-copper composite materials, and particularly relates to a tungsten-copper charge liner and a preparation method thereof. Background Art

[0002] The armor-piercing process of the shaped charge warhead is a precise and complex process. As one of the key components of the shaped charge warhead, the liner is the main component for forming the jet. The structure and material of the liner have a significant impact on the armor-piercing performance. The tungsten copper liner has been widely used in the oil perforation industry because the jet formed has a high head velocity and good continuity. However, the density difference between tungsten powder and copper powder is large. During the molding process, due to the effect of gravity, it is easy to cause uneven density distribution. In addition, the differences in particle size, microscopic shape, grain structure, lattice defects, etc. between the two will directly affect the density, particle size grading, fluidity, compressibility and formability of the liner during the preparation process, thereby affecting the jet performance of the liner. The oil perforating shaped charge warhead has increasingly higher requirements for the depth of penetration of the shaped charge jet into the target plate.

[0003] The existing tungsten powder and copper powder particle size and morphology are usually paid attention to separately, and their compounding is less concerned, resulting in poor fluidity and formability of the material formed after mixed molding, and the density of the formed charge liner is difficult to meet expectations. At the same time, the common tungsten copper charge liner has insufficient armor-piercing power and cannot meet the perforation penetration requirements. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a tungsten copper liner in view of the shortcomings of the above-mentioned prior art. The tungsten copper liner of the present invention optimizes the morphology and particle size distribution of tungsten powder and copper powder, and adds a modifier to ensure that the modified powder has good uniformity and fluidity, so as to have excellent forming performance, and combines the addition of energetic materials to achieve secondary reaction synergy, further improves the penetration depth of the tungsten copper liner, and solves the problem that the existing tungsten copper modified powder has poor fluidity and formability, and the perforation penetration depth of the liner prepared therefrom does not meet the requirements.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a tungsten copper liner, characterized in that the raw materials include the following components by mass: 70-90 parts of tungsten powder, 10-30 parts of copper powder, and 2-10 parts of energetic material; the energetic material is selected from at least one of Ni, Zr, and Ti, the ratio of the bulk density of the tungsten powder to the copper powder is 7.8-8.5: 1.8-1.95, and the tungsten powder is a spherical particle, and the copper powder is a dendritic structure. By controlling the morphology of the tungsten powder, it has better fluidity and reduces molding defects.

[0006] The above-mentioned tungsten-copper charge liner is characterized in that the ratio of the particle size D50 of the tungsten powder and the copper powder is 38~55:38~48.

[0007] The above-mentioned tungsten copper liner is characterized in that the mass purity of the tungsten powder is not less than 99.95%, the particle size is: D10=20μm~27μm, D50=38μm~50μm, D90=51μm~60μm, and the bulk density is 7.8g / cm 3 ~8.5g / cm 3 , the Hall flow rate does not exceed 25s / 50g; the particle size of the copper powder is: D10=15μm~22μm, D50=38μm~48μm, D90=74μm~81μm, and the bulk density is 1.8g / cm 3 ~1.95g / cm 3 .

[0008] The present invention controls the particle size and bulk density of tungsten powder and copper powder to avoid the raw material powder from being too fine and agglomerating or adhering to the surface of larger particles, thereby affecting the dispersion effect, and to avoid the raw material powder from being too coarse and causing poor fluidity.

[0009] The above-mentioned tungsten copper liner is characterized in that the tungsten powder, copper powder and energetic material are all modified by a modifier, and the modifier is selected from one or more of stearic acid, titanate coupling agent, silane coupling agent, aminosulfonic acid, ethylene-vinyl acetate copolymer and PEG, and the added mass of the modifier is 1% to 2% of the total mass of the tungsten powder, copper powder and energetic material.

[0010] The above-mentioned tungsten copper liner is characterized in that the density of the tungsten copper liner is not less than 95%, and the penetration depth used in the static armor penetration test is not less than 760mm.

[0011] At the same time, the present invention also discloses a method for preparing the tungsten copper liner as described above, characterized in that the method comprises the following steps: Step 1: Mix tungsten powder, copper powder and energetic material to obtain a mixture, and dissolve a lubricant and a modifier with a solvent to obtain a solution; the lubricant is paraffin, and the solvent is gasoline and / or anhydrous ethanol; Step 2: adding the solution in step 1 to the mixture, stirring and modifying the mixture while keeping warm, and drying and sieving to obtain modified powder; Step three, shaping the modified powder obtained in step two into a liner blank, and then degreasing and sintering to obtain a tungsten copper liner.

[0012] The above-mentioned preparation method is characterized in that the particle size D50 of the modified powder in step 2 is 40μm~55μm, and the bulk density is 5g / cm 3 ~8g / cm 3 , water contact angle is greater than 120°.

[0013] The above-mentioned preparation method is characterized in that the modification temperature in step 2 is 60°C to 90°C, the modification time is 60min to 120min, and the stirring speed is 100r / min to 200r / min.

[0014] The above-mentioned preparation method is characterized in that the molding process in step three is spin molding, and the female mold speed is 580r / min~620r / min, the pressure is 15MPa~30MPa, and the single feed amount requirement is 70g±5g~90g±5g.

[0015] The above-mentioned preparation method is characterized in that the modified powder in step 3 is fed by automatic online weighing of metal powder and is formed by centrifugal strong pressure rotation.

[0016] Compared with the prior art, the present invention has the following advantages: 1. The tungsten-copper charge liner of the present invention optimizes the morphology and particle size distribution of tungsten powder and copper powder, so that the blank prepared from the raw materials will not occupy a large space volume, ensuring that the automatic pressing loading requirements are met during the molding process. While improving the moldability of tungsten powder, it is also beneficial to reduce the ultimate pressing pressure of the modified powder, solving the problem of the limited fluctuation of the modified powder quality by the charge liner.

[0017] 2. By adding energetic materials to the tungsten copper charge liner of the present invention, a large amount of heat is released in a very short time during the armor-piercing process, and high-pressure gas is generated, which has a self-cleaning effect on the perforation, and is beneficial to improving the penetration depth of the tungsten copper charge liner.

[0018] 3. The tungsten powder, copper powder and energetic material in the tungsten-copper charge liner of the present invention are modified by a modifier, and the modifier is used to generate hydroxyl groups on the surface of the metal particles, so that the tiny powder is not easy to agglomerate, ensuring that the modified powder has good uniformity and fluidity, so that the charge liner blank obtained by molding the modified powder has no obvious defects; at the same time, by adding a lubricant such as paraffin, the lubricity of the modified powder is greatly improved, ensuring that the demolding process after molding is carried out smoothly and does not stick to the wall.

[0019] 4. The added modifier and lubricant of the present invention are removed through the sintering process, and do not react chemically with tungsten during the sintering process. No free diffused carbon impurities are generated during the removal stage, and the removal is relatively thorough. The tungsten copper charge liner finally obtained has excellent performance, a density of 92% to 99%, and a penetration depth of more than 760 mm in the static armor penetration test, which can meet the needs of oil perforation.

[0020] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0021] The tungsten powder used in Examples 1 to 3 of the present invention was purchased from Zigong Cemented Carbide Co., Ltd., with the model number CTP crystalline tungsten, which is spherical; the copper powder used was purchased from Chongqing Youyan Chongye New Materials Co., Ltd., with the model number FTD-200, and has a dendritic structure; the titanium powder was purchased from Sichuan Henghui New Materials Technology Co., Ltd., with the model number TF-0; the nickel powder was purchased from Jinchuan Group Co., Ltd., with the model number FNiT04; the zirconium powder was purchased from Beijing Xingrongyuan Technology Co., Ltd., with the model number XH-Zr-01; the particle sizes of the three energetic materials Ni, Zr, and Ti are executed with reference to the requirements for copper powder.

[0022] Example 1 The tungsten copper liner of this embodiment includes the following raw materials by mass: 80 parts of tungsten powder, 18 parts of copper powder, and 2 parts of titanium powder; the mass purity of the tungsten powder is 99.96%, the particle size D10=26.58μm, D50=45.62μm, D90=58.64μm, and the bulk density is 7.8g / cm 3 , the Hall flow rate is 20s / 50g; the particle size of the copper powder is D10=19.01μm, D50=44.87μm, D90=77.90μm, and the bulk density is 1.95g / cm 3 .

[0023] The method for preparing the tungsten copper liner in this embodiment comprises the following steps: Step 1: Add 80g of tungsten powder, 18g of copper powder and 2g of titanium powder into a mixer at room temperature and mechanically mix them for 4h at a rotation speed of 50r / min to obtain a mixture; add 1g of titanate coupling agent into 25mL of industrial gasoline and hydrolyze at 80°C for 60min, then add 1% of the paraffin solution by mass of the mixture, stir for 60min to mix evenly, then heat to 80°C and keep warm for 60min to obtain a solution; Step 2: Add the solution in step 1 to the mixture, perform modification at a stirring speed of 100 r / min, a modification temperature of 90°C, a modification time of 120 min, keep warm after modification, dry at 60°C for 2 h, and pass through an 80-mesh sieve to obtain modified powder; Step 3: The modified powder obtained in step 2 is fed by automatic online weighing of metal powder, and the blank of the liner is obtained by centrifugal strong pressure rotation molding, i.e., spinning molding, and the female mold speed is 580r / min, the pressure is 20MPa, and the single feed amount is 70g±5g. Then, it is degreased at 600°C and hydrogen sintered at 1200°C to obtain a tungsten copper liner.

[0024] The modifier in this embodiment can also be one or more of stearic acid, titanate coupling agent, silane coupling agent, aminosulfonic acid, ethylene-vinyl acetate copolymer and PEG in addition to titanate coupling agent; the solvent of the modifier can also be anhydrous ethanol, or gasoline and anhydrous ethanol.

[0025] Example 2 The tungsten copper liner of this embodiment includes the following raw materials by mass: 80 parts of tungsten powder, 16 parts of copper powder, and 4 parts of nickel powder; the mass purity of the tungsten powder is 99.96%, the particle size D10=21.65μm, D50=39.41μm, D90=52.31μm, and the bulk density is 8.5g / cm 3 , the Hall flow rate is 23s / 50g; the particle size of the copper powder is D10=16.98μm, D50=39.72μm, D90=75.54μm, and the bulk density is 1.82g / cm 3 .

[0026] The method for preparing the tungsten copper liner in this embodiment comprises the following steps: Step 1: Add 80g of tungsten powder, 16g of copper powder and 4g of nickel powder into a mixer at room temperature and mechanically mix them for 4h at a rotation speed of 50r / min to obtain a mixture; add 2g of titanate coupling agent into 25mL of industrial gasoline and hydrolyze at 80°C for 60min, then add 1% of the paraffin solution by mass of the mixture, stir for 60min to mix evenly, then heat to 80°C and keep warm for 60min to obtain a solution; Step 2: Add the solution in step 1 to the mixture, perform modification at a stirring speed of 150 r / min, a modification temperature of 80° C., a modification time of 80 min, keep warm after modification, dry at 60° C. for 2 h, and pass through an 80-mesh sieve to obtain modified powder; Step 3: The modified powder obtained in step 2 is fed by automatic online weighing of metal powder, and the blank of the liner is obtained by centrifugal strong pressure rotation molding, i.e., spinning molding, and the female mold speed is 620r / min, the pressure is 15MPa, and the single feed amount is 90g±5g. Then, it is degreased at 600°C and hydrogen sintered at 1350°C to obtain a tungsten copper liner.

[0027] Example 3 The tungsten copper liner of this embodiment includes the following raw materials by mass: 80 parts of tungsten powder, 16 parts of copper powder, and 4 parts of zirconium powder; the mass purity of the tungsten powder is 99.95%, the particle size D10=24.07μm, D50=40.87μm, D90=55.07μm, and the bulk density is 8.2g / cm 3, the Hall flow rate is 24s / 50g; the particle size of the copper powder is D10=20.30μm, D50=46.72μm, D90=79.93μm, and the bulk density is 1.87g / cm 3 .

[0028] The method for preparing the tungsten copper liner in this embodiment comprises the following steps: Step 1: Add 80g of tungsten powder, 16g of copper powder and 4g of zirconium powder into a mixer at room temperature and mechanically mix for 4h at a rotation speed of 50r / min to obtain a mixture; add 1.5g of titanate coupling agent into 25mL of industrial gasoline and hydrolyze at 80°C for 60min, then add 1% of the paraffin solution by mass of the mixture, stir for 60min to mix evenly, then heat to 80°C and keep warm for 60min to obtain a solution; Step 2: Add the solution in step 1 to the mixture, perform modification at a stirring speed of 200 r / min, a modification temperature of 60°C, a modification time of 60 min, keep warm after modification, dry at 60°C for 2 h, and pass through an 80-mesh sieve to obtain modified powder; Step 3: The modified powder obtained in step 2 is fed by automatic online weighing of metal powder, and the blank of the liner is obtained by centrifugal strong pressure rotation molding, i.e., spinning molding, and the female mold speed is 600r / min, the pressure is 30MPa, and the single feed amount is 90g±5g. Then, it is degreased at 600℃ and hydrogen sintered at 1300℃ to obtain a tungsten copper liner.

[0029] Comparative Example 1 The difference between this comparative example and Example 1 is that no energetic material titanium powder is added.

[0030] Comparative Example 2 The difference between this comparative example and Example 1 is that the modification in step 2 is not performed, and the mixed material in step 1 is directly subjected to the molding, degreasing and sintering processes in step 3.

[0031] Comparative Example 3 The difference between this comparative example and Example 1 is that the tungsten powder in Example 1 is replaced by reduced tungsten powder produced by Zigong Cemented Carbide Co., Ltd., with a grade of FW-1, a mass purity of 99.95%, a particle size of D10=3.34μm, D50=8.40μm, D90=19.16μm, a Hall flow rate of 24s / 50g, and a bulk density of 3.55g / cm 3 .

[0032] The tungsten copper liner in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 was tested for its compactness, loose density, particle size, penetration depth, and water contact angle. The results are shown in Table 1.

[0033] 1. Density The volume of the tungsten copper liner was measured by the Archimedes displacement method, and then the density and compactness of the liner were calculated; the electronic analytical balance used had an accuracy of 0.1 mg and a range of 200 g.

[0034] Density calculation formula: R=ρ 实际 / r 理论 .

[0035] 2. Penetration Depth After the tungsten copper charge liner was compressed, static armor penetration tests were carried out at the same blasting height. After the static armor penetration test, the 60# steel target plate was cut open along the direction parallel to the jet incidence, the penetration depth of the shaped energy jet in the steel target was measured with a measuring tool, and the macroscopic destruction characteristics of the target plate were observed.

[0036] 3. Water contact angle The test was carried out using a G-1 goniometer contact angle tester produced by Kyowa Corporation of Japan. The modified powder was prepared into a powder compact with a diameter × height of 30 mm × 10 mm by a molding method. Deionized water was dropped on the surface of the powder compact for 1 minute before the test. Each sample was measured at 3 points with a spacing of 5 mm, and a total of 6 readings were taken and the average value was taken.

[0037] 4. Bulk density The bulk density of tungsten powder and copper powder was determined according to GB / T1479.1-2011 "Determination of bulk density of metal powders Part 1: Funnel method". The powder was allowed to flow naturally through a 2.5 mm standard funnel with a volume of 25 cm. 3 The ratio of the mass of powder to the volume of a cylindrical standard metal measuring cup is the bulk density.

[0038] 5. Particle size and the proportion of particles in particle size distribution The particle size of the metal powder sample was characterized by using the Bettersize2000 laser particle size analyzer to obtain the particle size distribution characteristics of the metal powder; the dry method was used for measurement, with air as the dispersion medium, among which D10, D50 and D90 are typical parameters for characterizing the cumulative particle size distribution of the powder; the laser particle size tester was used to test the powder particle size by dry method, and the specific gravity within the particle size range was calculated.

[0039] Table 1

[0040] In Table 1: A is the ratio of the bulk density of tungsten powder to that of copper powder; B is the ratio of the particle size D50 of tungsten powder to that of copper powder; D50 改 is the D50 particle size of the modified powder; ρ is the bulk density of the modified powder; r is the water contact angle of the modified powder; R is the density of the sintered charge liner.

[0041] It can be seen from Table 1 that compared with Comparative Example 1, the static armor penetration test penetration depth of the tungsten copper liner after adding the energetic material in Example 1 increases; compared with Comparative Example 2, the loose density of the sintered liner after adding the modifier in Example 1 increases, and the density of the liner increases; at the same time, the modified powder used in Comparative Example 3 has a smaller loose density, and the liner wall prepared at the same loading amount is too thick and cannot meet the liner shape size requirements.

[0042] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A tungsten copper liner, characterized in that: The raw materials include the following components by mass: 70-90 parts of tungsten powder, 10-30 parts of copper powder, and 2-10 parts of energetic material; the energetic material is selected from at least one of Ni, Zr, and Ti, the bulk density ratio of the tungsten powder to the copper powder is 7.8-8.5: 1.8-1.95, the tungsten powder is spherical particles, and the copper powder is a dendritic structure.

2. The tungsten copper liner according to claim 1 is characterized in that: The ratio of the particle size D50 of the tungsten powder to the copper powder is 38-55:38-48.

3. The tungsten copper liner according to claim 1, characterized in that: The mass purity of the tungsten powder is not less than 99.95%, the particle size is: D10=20μm~27μm, D50=38μm~50μm, D90=51μm~60μm, and the bulk density is 7.8g / cm 3 ~8.5g / cm 3 , the Hall flow rate does not exceed 25s / 50g; the particle size of the copper powder is: D10=15μm~22μm, D50=38μm~48μm, D90=74μm~81μm, and the bulk density is 1.8g / cm 3 ~1.95g / cm 3 .

4. The tungsten copper liner according to claim 1, characterized in that: The tungsten powder, copper powder and energetic material are all modified by a modifier, and the modifier is selected from one or more of stearic acid, titanate coupling agent, silane coupling agent, aminosulfonic acid, ethylene-vinyl acetate copolymer and PEG, and the added mass of the modifier is 1% to 2% of the total mass of the tungsten powder, copper powder and energetic material.

5. The tungsten copper liner according to claim 1 is characterized in that: The density of the tungsten copper liner is not less than 95%, and the penetration depth used in static armor penetration test is not less than 760mm.

6. A method for preparing a tungsten copper liner according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: Step 1: Mix tungsten powder, copper powder and energetic material to obtain a mixture, and dissolve a lubricant and a modifier with a solvent to obtain a solution; the lubricant is paraffin, and the solvent is gasoline and / or anhydrous ethanol; Step 2: adding the solution in step 1 to the mixture, stirring and modifying the mixture while keeping warm, and drying and sieving to obtain modified powder; Step three, shaping the modified powder obtained in step two into a liner blank, and then degreasing and sintering to obtain a tungsten copper liner.

7. The preparation method according to claim 6, characterized in that: The particle size D50 of the modified powder in step 2 is 40 μm-55 μm, and the bulk density is 5 g / cm 3 ~8g / cm 3 , water contact angle is greater than 120°.

8. The preparation method according to claim 6, characterized in that: The modification temperature in step 2 is 60°C to 90°C, the modification time is 60min to 120min, and the stirring speed is 100r / min to 200r / min.

9. The preparation method according to claim 6, characterized in that: The molding process described in step three is spin molding, and the female mold speed is 580r / min~620r / min, the pressure is 15MPa~30MPa, and the single feed amount requirement is 70g±5g~90g±5g.

10. The preparation method according to claim 6, characterized in that: The modified powder in step three is fed by automatic online weighing of metal powder and is formed by centrifugal strong pressing and rotation.

Citation Information

Patent Citations

  • Method for manufacturing powder metallurgy shaped charge liner for oil-gas well jet cutter

    CN103586474A

  • Preparation method for tungsten copper nickel alloy powder

    CN105057681A

  • High-copper W-Ni-Cu alloy material and preparation method thereof

    CN107988543A

  • Production of tungsten-based sintered heavy alloy

    JP1995278693A

  • Injection molded shaped charge liner

    US20090071361A1

Cited By

  • Tungsten copper alloy and preparation method thereof

    CN121718738A